Digital Technology for Non-Formal Learning during the Covid 19 Pandemic - Sutikno Sutikno; Saiful Anwar Matondang; Rosmawati Harahap (AL-ISHLAH: Jurnal Pendidikan, 2022)
Non-formal schooling was affected during the Covid-19 pandemic. The goal of this study was to look at how digital technology may be used in the Non-Formal Education Program. We looked at how digital technology is transforming traditional labor structures and transitioning them to online models using a literature study. According to the data, digital technology has an influence on home learning (LFH). Because of the advent of digital technology, students are utilizing online programs to replace face-to-face educational paradigms. Both the non-formal and formal education models have benefits, such as instructors' digital competency in building online course programs, knowledge of parents' digital modes, and the potential of students' networks to study with digital devices. The right technique for all schooling must be devised. However, it has various flaws, including low motivation and poor skill development if not used in conjunction with the appropriate approach. As a result, for the online learning process to be successful, especially in non-formal education, the correct method must be developed.